Artistic Representation of Russian National-Cultural Concept of BLOOD in Works of Mikhail Lermontov - T. B. Radbil; I. S. Yukhnova (Научный диалог)
This study examines the distinctive authorial representation of the national-cultural concept of BLOOD in Mikhail Lermontov’s literary works. The research aims to analyze the semantic content of this concept within the Russian linguistic worldview and trace its transformation in Lermontov’s artistic system. The investigation draws upon encyclopedic sources, lexicographical materials, and Lermontov’s poetic and prose texts. The findings demonstrate that Lermontov’s literary universe incorporates nearly all semantic components of the Russian cultural concept of BLOOD: notions of kinship and shared ancestry, metaphors of death (particularly violent death), the semantics of blood vengeance, and expressions of extreme emotional intensity. The study reveals that Lermontov’s creative contribution expands the conceptual boundaries through: - The portrayal of blood as a complex amalgam of kinship, love, vengeance, and rebellion; - The use of blood symbolism in nature descriptions as metaphorical expressions of suffering, martyrdom, and evil; - The embodiment in blood imagery of supernatural forces invading human existence and manifestations of otherworldliness.